Clinical practice guidelines for the screening and management of adults with malnutrition or risk of malnutrition in the Peruvian social security system (EsSalud) - Holguín Marín, Rosario A. (2022)
Introduction: This article summarizes the clinical practice guide (CPG) for the screening and management of malnourished patients or patients at risk of malnutrition in the Social Security of Peru (EsSalud). Objective: To provide clinical recommendations based on evidence for the screening and management of malnourished patients or patients at risk of malnutrition in EsSalud. Methods: A CPG for the screening, management and monitoring of malnourished patients or patients at risk of malnutrition in EsSalud was developed. To this end, a guideline development group (local GDG) was established, including medical specialists and methodologists. The local GDG formulated 9 clinical questions to be answered by this CPG. Systematic searches of systematic reviews and -when it was considered pertinent- primary studies were conducted in Pubmed and CENTRAL during 2021. The evidence to answer each of the posed clinical questions was selected. The quality of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the local GDG used the GRADE methodology to review the evidence and formulate the recommendations, points of good clinical practice, and the flowchart of screening and management. Finally, the CPG was approved with Resolution No. 128-IETSI-ESSALUD-2021. Results: This CPG addressed 9 clinical questions, divided into three topics: screening, management and monitoring of malnourished patients or patients at risk of malnutrition. Based on these questions, 6 recommendations (3 strong recommendations and 3 weak recommendations), 39 points of good clinical practice, and 2 flowcharts were formulated. Conclusion: This article summarizes the methodology and evidence-based conclusions from the CPG for the screening, management and monitoring of malnourished patients or patients at risk of malnutrition in EsSalud.